The Effect Of Work Engagement, Work Stress, and Motivation on Employee Performance of PT. Daria Dharma Pratama Ipuh - Nining Septia; Karona Cahya Susena; Muhammad Rahman Febliansa (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of work engagement, work stress, and motivation on the employee performance of PMKS Ipuh PT. Daria Dharma Pratama. The research employed a quantitative approach with an explanatory research design and multiple linear regression analysis using IBM SPSS version 25. The research population consisted of 117 permanent employees, with a saturated sampling technique applied. Data were collected through a questionnaire using a 5-point Likert scale and analyzed through validity tests, reliability tests, multiple linear regression analysis, t-test (partial), F-test (simultaneous), and coefficient of determination (R²). The results show that work engagement has a positive and significant effect on employee performance (β = 0.184; p = 0.012), work stress has a negative and significant effect (β = −0.075; p = 0.035), and motivation is the most dominant predictor with a positive and significant effect (β = 0.369; p = 0.000). Simultaneously, the three variables significantly affect employee performance (F = 43.313; p = 0.000) with a coefficient of determination of 53.5%. The study concludes that motivation serves as the primary driver of performance, while work engagement acts as a facilitating condition and work stress functions as an inhibiting factor requiring management. Integrated and holistic human resource management interventions are recommended, with priority given to enhancing motivation, maintaining work engagement, and implementing comprehensive stress management programs.